The wolf of Snow Hollow [videorecording (DVD)] - Cummings, Jim (Film director); Cummings, Jim (Film director); Cummings, Jim (Film director); Lindhome, Riki, 1979-; Forster, Robert, 1942-2019; East, Chloe (Warner Bros. Entertainment, 2020)
When dead bodies start appearing after each full moon, a stressed-out police officer struggles to overcome the belief that a werewolf is in town.